DESIGN OF WFOIL 18 ALBATROSS WITH HYDROGEN TECHNOLOGIES - Zore, Nejc; Avsec, Jurij; Novosel, Urška (Journal of Energy Technology, 2025)
This article discusses the design of fuel cell propulsion for 18 albatross foil vessels. The purpose of this article determined the economic viability of such propulsion. WFoil 18 Albatross was chosen for a high-speed, low-power propulsion system.The hydrogen propulsion system for the Albatross vessel consists of the following parts:Electric motor (Emrax 188) to convert electricity into mechanical energy;Battery (LG RESU 3.2EX | LG Battery System), which provides electricity in case of emergency or adds the necessary energy to run the engine at maximum power;Controller (EmDrive 500), which provides enough energy to pass between the elements of the propulsion system;Fuel cell (Hydrogenics HYPM-HD 30 POWER MODULE), which is the primary source of energy;The tank (tank for hydrogen gas type 3) stores fuel, which in our case is hydrogen.The brackets indicate the parts that have been selected for the hydrogen propulsion system. The approximate weight of all these parts is about 249.1 kg and the price of all these parts is about 55254 €. All prices are from 2020 and are subject to change. The main idea in the construction of this charging station is the use of seawater and solar energy or renewable energy sources for hydrogen production. The components of the charging station are Solar cells (LG NeON 2), Desalination (CRYSTAL EX PURE), Electrolysis (Nel C Series C10), and Charging station (Haskel (Version with air compressor)). The brackets indicate the parts that have been selected for the charging station. The approximate weight of all these parts is about 10236 kg and the price of all these parts is about 517664 €. All prices are from 2020 and are subject to change.